PEDOGEOMORPHOLOGICAL SYSTEMS IN THE INTERPRETATION OF THE EVOLUTION OF QUATERNARY LANDSCAPES IN HUMID TROPICAL CLIMATES - Rubira, Felipe Gomes; Barreiros, André Mateus; Villela, Fernando Nadal Junqueira; Perez Filho, Archimedes (Mercator, 2019)
There is always a relationship between soil and relief in the landscapes of humid tropical and subtropical climates, due to the thick mantles of regolith resulting from accelerated physical, chemical, and biological weathering. It is important to investigate pedogeomorphological systems in the systemic analyses of the origin and modeling processes of the terrestrial surface. This paper seeks to establish the central relationships between Geomorphology and Pedology, and the importance of pedogeomorphological systems in the evolutionary interpretation of quaternary landscapes in humid tropical climates. Thus, the discussions address the influence of landforms on soil formation and spatialization and the pedological impacts on the modification of relief forms, as well as the methodological support from Pedology to Geomorphology concerning the evolutionary interpretation of tropical landscapes. Therefore, there is evidence of the need for closer links between the studies of geomorphological and pedological systems in the analysis of tropical landscapes. Keywords : Geomorphology, Pedology, Morphogenesis, Pedogenesis, Structural Analysis of Pedological Cover.